Strategy for Forming Religious Character Through The IPNU – IPPNU Organization - Achmad Latif Nur Khakim; Yuyun Bahtiar; Emi Lilawati (SCHOOLAR: Social and Literature Study in Education, 2025)
This study aims to analyze the strategy of religious character formation in adolescents through the Nahdlatul Ulama Student Association (IPNU) and Nahdlatul Ulama Female Student Association (IPPNU) Mojokrapak Branch. The research method used is descriptive qualitative with a case study approach. Data collection was carried out through observation, interviews, and documentation. The results of the study indicate that IPNU - IPPNU plays a strategic role in forming religious character through various religious activities, such as regular religious studies, reading training, and worship habituation programs. The implementation of these religious values can be seen in the attitudes and behavior of members who are increasingly devout in worship, tolerant, and have better personalities. Supporting factors include a religious environment, support from clerics, and the spirit of cadre formation. This study concludes that the IPNU-IPPNU organization in Mojokrapak has succeeded in becoming an effective forum for forming the religious character of the younger generation.